(untitled) - Dulan, Steven W. (New York, 2009)
One of the most widely-taken tests in the United States and around the world, the GRE is crucial for your graduate school entrance-and McGraw-Hill's GRE is the your comprehensive study tool. Created by test-preparation specialists at Advantage Education, it gives you the most up-to-date information on each section of the test. From practice tests and skill-building techniques to expert coaching, essay help and online practice, you'll have all the guidance you need.
Keywords: Graduate record examination,Universities and colleges,Hồ sơ thi sau đại học,Đại học và Cao đẳng; Graduate work,Examinations,Nghiên cứu sinh,Kỳ thi